2017
DOI: 10.1039/c7ta07116g
|View full text |Cite
|
Sign up to set email alerts
|

Formic acid oxidation on platinum electrodes: a detailed mechanism supported by experiments and calculations on well-defined surfaces

Abstract: The key elements in the mechanism of the formic acid oxidation reaction on platinum have been completely elucidated, not only for the direct path through an active intermediate, but also for the CO formation route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
139
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 94 publications
(163 citation statements)
references
References 65 publications
10
139
0
10
Order By: Relevance
“…However, CO can be also easily to be formed and accumulated on pure Pt(111), which can lead to blocking and poisoning of surface active sites, explaining why the experimentally measured HCOOH oxidation currents are still low on pure Pt electrodes even if at low overpotentials. Thus, our recent study confirmed previous experimental and theoretical conclusions on HCOO as intermediates and CO poison effect on pure Pt electrode . Similarly, three possibilities are considered and the corresponding MEP analyses are carried out on Ru@Pt(111) starting from HCOOH initial oxidation, as shown in Figure (a).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…However, CO can be also easily to be formed and accumulated on pure Pt(111), which can lead to blocking and poisoning of surface active sites, explaining why the experimentally measured HCOOH oxidation currents are still low on pure Pt electrodes even if at low overpotentials. Thus, our recent study confirmed previous experimental and theoretical conclusions on HCOO as intermediates and CO poison effect on pure Pt electrode . Similarly, three possibilities are considered and the corresponding MEP analyses are carried out on Ru@Pt(111) starting from HCOOH initial oxidation, as shown in Figure (a).…”
Section: Resultssupporting
confidence: 84%
“…The previous experimental studies have concluded that HCOOH oxidation on pure Pt electrodes can evolve via a triple‐path mechanism in acidic electrolyte, namely, a direct pathway, in which HCOOH is oxidized directly into CO 2 by dehydrogenation; an indirect pathway, in which the strongly adsorbed CO is formed through dehydration and further oxidized into CO 2 ; a formate pathway, including formate formation and further oxidation into CO 2 . However, even if on pure Pt electrodes, the measured oxidation current is still low.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this study allows for a better understanding of formate adsorption and electrooxidation of formate/formic acid on metallic surfaces. The approach of studying the adsorption behaviour of unreactive adsorbates to understand those of reactive ones has been found to be extremely valuable and can be applied to other surfaces, such as Pt(111) for example …”
Section: Discussionmentioning
confidence: 99%
“…The approach of studying the adsorption behaviour of unreactive adsorbates to understand those of reactive ones has been found to be extremely valuable and can be applied to other surfaces, such as Pt(111) for example. [73] Experimental Section…”
Section: Discussionmentioning
confidence: 99%
“…The current density was also on the basis of the Pt weight coated on the GC electrode. The formic acid electro‐oxidation over Pt catalysts was in accordance with the dual path, namely, the direct dehydrogenation process (HCOOH→CO 2 +2H + +2e − ) and dehydration process with poisonous CO produced (HCOOH→CO ads +H 2 O).…”
Section: Resultsmentioning
confidence: 73%